2019
DOI: 10.1101/540450
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Progranulin deficiency leads to reduced glucocerebrosidase activity

Abstract: Mutation in the GRN gene, encoding the progranulin (PGRN) protein, shows a dose-dependent disease correlation, wherein haploinsufficiency results in frontotemporal lobar degeneration (FTLD) and complete loss results in neuronal ceroid lipofuscinosis (NCL). Although the exact function of PGRN is unknown, it has been increasingly implicated in lysosomal physiology. Here we report that PGRN interacts with the lysosomal enzyme, glucocerebrosidase (GBA), and is essential for proper GBA activity. GBA activity is sig… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 65 publications
3
19
0
Order By: Relevance
“…Moreover, chemical [ 75 ] or genetic inhibition [ 61 ] of β-glucocerebrosidase (GBA; GCase) activity leading to the accumulation of glucosylceramides also causes increased expression of GPNMB. Progranulin deficiency reduces glucocerebrosidase activity [ 116 , 134 ] suggesting that the accumulation of glucosylceramide or other sphingolipids could be a proximal cause of GPNMB upregulation in the Grn −/− mouse brain, an idea that needs further investigation. Although the precise mechanism that causes GPNMB upregulation in progranulin deficiency is unclear, our data suggest that measurement of GPNMB levels in the CSF could be used to monitor changes in microglial activation and response to therapies in FTD- GRN patients, similar to substrate reduction therapy in lysosome storage disorders [ 71 , 78 , 119 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, chemical [ 75 ] or genetic inhibition [ 61 ] of β-glucocerebrosidase (GBA; GCase) activity leading to the accumulation of glucosylceramides also causes increased expression of GPNMB. Progranulin deficiency reduces glucocerebrosidase activity [ 116 , 134 ] suggesting that the accumulation of glucosylceramide or other sphingolipids could be a proximal cause of GPNMB upregulation in the Grn −/− mouse brain, an idea that needs further investigation. Although the precise mechanism that causes GPNMB upregulation in progranulin deficiency is unclear, our data suggest that measurement of GPNMB levels in the CSF could be used to monitor changes in microglial activation and response to therapies in FTD- GRN patients, similar to substrate reduction therapy in lysosome storage disorders [ 71 , 78 , 119 ].…”
Section: Discussionmentioning
confidence: 99%
“…These granulin peptides have been proposed to possess unique biological activities, in a way similar to the saposin peptides derived from PSAP, which function as activators for enzymes involved in glycosphingolipid degradation (O'Brien & Kishimoto, 1991). In line with this, PGRN and granulin peptides have been shown to regulate the activities of several lysosome enzymes, including cathepsin D (Beel et al, 2017;Butler et al, 2019;Valdez et al, 2017;Zhou et al, 2017a) and glucocerebrosidase (Arrant et al, 2019;Valdez et al, 2019;Zhou et al, 2019).…”
Section: Introductionmentioning
confidence: 89%
“…Heterozygous mutations in GRN lead to the development of frontotemporal dementia (FTD) and homozygous mutations cause the lysosomal storage disorder, neuronal ceroid lipofuscinosis [35][36][37]. In addition to its role in regulating a multitude of functions including embryogenesis, tumorigenesis, inflammation and wound repair [38,39], recent studies have identified its role in lysosomal function as a chaperone of several lysosomal enzymes such as GCase [40,41], cathepsin D [42] and Hex A [43]. Two modes of regulation of GBA by PGRN have been identified so far.…”
Section: Introductionmentioning
confidence: 99%